Effect of Fuel-to-Oxygen Ratio to Tungsten Carbide-Nickel (WC-Ni) High Velocity Oxy Fuel (HVOF) Deposition - Harimon, Mohd Azhar; Basri, Siti Nurmasyhura; Halmi, Mohamad Ariff Mohd (Research Progress in Mechanical and Manufacturing Engineering, 2021)
Carbon steel widely used in the industrial world at diverse applications such as marine, nuclear/fossil fuel power plants, shipping, chemical processing, mining, building, and metal processing equipment. The surface of carbon steel easy to rust towards time cause by high temperature and environmental surrounding that consists air and the solution of the problem is use coating to protect the carbon steel. High velocity oxy – fuel was use for method of coating and base of material coating use during coating process is powder. Therefore, the first objective of the study is to determine the suitable value of the oxygen to fuel ratio on WC-Ni coating but to make sure WC-Ni coating is the best coating, The coating material use for this investigation such as tungsten carbide-nickel (WC-Ni) and tungsten carbide-cobalt chromium (WC-CoCr) coating will use to make the comparison on wear and hardness test that focus only High velocity oxy-fuel (HVOF) method. The second objective of the study is to determine suitable type of fuel used on coating spray on porosity, hardness, particle velocity, and particle temperature. The effect of fuel to oxygen ratio can see on image of porosity of scanning electron microscope (SEM). Coating with the higher hardness value combined with the lower wear is attainable for fuel-to-oxygen ratio about 1.3 and kerosene fuel is suitable for coating process.